Union decline in Britain: Is chauvinism also to blame? - Getinet Astatike Haile (Institute for the Study of Labor (IZA), 2012)
The paper examines if workplace gender diversity offers some explanation for the decline of unions in Britain. Using the WERS2004 linked employer-employee data and alternative econometric estimators it reports an inverse relationship between workplace union density and gender diversity. Gender and ownership status based sub-group analyses suggest the inverse relationship to be stronger for male union members and those in the private sector. Gender group size based analysis reveals a positive link between workplace union density and gender diversity in workplaces with a female majority. The findings in this paper may mean that unions (and their main constituents, men) may need to embrace the changing workplace demography genuinely to improve their fate.
urn:nbn:de:101:1-201208174805
Keywords: J51; J16; J82; 330; trade union decline; gender diversity; linked employer-employee data; Britain; Gewerkschaftsmitgliedschaft; Gleichstellungspolitik; Geschlecht; Diversity Management; Schätzung; Großbritannien